Analisis Penggunaan Model Pembelajaran Paired Story Telling dalam Keterampilan Bercerita Peserta Didik pada Pembelajaran Tematik Integratif di Kelas 3 SD Kanisius Karang Bangun - Margareta Vita Ningsih; Sri Handayani; Oktiana Handini (Journal on Education, 2022)
The purpose of this study was to determine the use of the Paired Story Telling learning model in the storytelling skills of students in integrative thematic learning, to find out the advantages and disadvantages of using the Paired Story Telling learning model in the storytelling skills of students in integrative thematic learning. The research method used is a type of qualitative research. The research subjects were grade 3 students. Data collection techniques were observation, interviews and documentation. The data analysis used was data reduction, data display and verifying. The validity of the data using the triangulation of sources and techniques credibility test. The results showed that the use of the Paired Story Telling learning model in the storytelling skills of students in integrative thematic learning in class 3 was stated in the good category, namely 50% because the teacher always invited students to do storytelling activities in the learning process. The advantages and disadvantages of the Paired Story Telling learning model in the storytelling skills of students in integrative thematic learning in grade 3 are that it can improve students' storytelling skills in integrative thematic learning.